DEIXIS FOUND IN MOVIE SCRIPT SING - Ni Made Dwipayani; I Ketut Subagia; Anak Agung Gede Suarjaya (Universitas Warmadewa, 2020)
The title of this paper is Deixis found in Movie Script Sing. In this paper, the writers try to analyze and discuss about the type, class words, and the use of deixis found in the movie script Sing. Data were collected from the movie script of Sing. The data were classified based on the types to Levinson’s Theory (1983). The specific aim of this paper is to describe and analyze the types of deixis in the movie script, analyze sentence by sentence. By doing this research it will be able to know more details about the types of deixis. Then analyzed, it was the types, class words and the use of deixis in the movie Sing. In collecting the data, observation method was applied. First the writer watched the movie than observed the subtitle in the movie. Then were quoted the selected data, and classified in accordance with their types of deixis. Based on the result of analysis, it was found there are five types of deixis, namely person deixis (including I, my, me, she, her, his, she, he, we, you, they), time deixis (including now), place deixis (including here), discourse deixis (including this, that), and social deixis (including mommy and grandpa).